2020
DOI: 10.1002/eap.2212
|View full text |Cite
|
Sign up to set email alerts
|

Fine sediment and flow velocity impact bacterial community and functional profile more than nutrient enrichment

Abstract: Freshwater ecosystems face many simultaneous pressures due to human activities. Consequently, there has been a rapid loss of freshwater biodiversity and an increase in biomonitoring programs. Our study assessed the potential of benthic stream bacterial communities as indicators of multiple-stressor impacts associated with urbanization and agricultural intensification. We conducted a fully crossed four-factor experiment in 64 flow-through mesocosms fed by a pristine montane stream (21 d of colonization, 21 d of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 101 publications
(149 reference statements)
0
3
0
Order By: Relevance
“…Therefore, environmental assessments in the basin should take both taxonomically and trait‐based approaches into consideration. Future knowledge could be gained by exploring the different facets of β ‐diversity in other aquatic organisms, such as fish and macroinvertebrates in large catchments, so that ecological studies can more extensively examine species interactions (e.g., co‐occurrence networks; Juvigny‐Khenafou et al, 2020) and other ecological processes (e.g., community assemblies; Chen et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, environmental assessments in the basin should take both taxonomically and trait‐based approaches into consideration. Future knowledge could be gained by exploring the different facets of β ‐diversity in other aquatic organisms, such as fish and macroinvertebrates in large catchments, so that ecological studies can more extensively examine species interactions (e.g., co‐occurrence networks; Juvigny‐Khenafou et al, 2020) and other ecological processes (e.g., community assemblies; Chen et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…DNA metabarcoding has become a valuable tool for gathering extensive amounts of microbial community data that would have been very costly or nearly impossible a few years ago [30][31][32][33][34]. Recent studies in freshwater environments have shown bacterial assemblage responses to nutrients [26,35,36], flow and fine sediment [37], temperature and pH [36], and conductivity [35].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing focus on multiple stressors and freshwater ecosystems in the Global South may likely lead to changes in observed international collaboration trends. For example, there are increasing numbers of multiple‐stressor studies conducted in China during the last 5 years (Pu, Zeng, Mo, Liao, & Chen, 2019; Pu, Zeng, Mo, He, et al, 2019; Liu et al, 2020; Juvigny‐Khenafou et al, 2020; Juvigny‐Khenafou, Piggott, Atkinson, Zhang, Wu, & Matthaei, 2021; Juvigny‐Khenafou, Piggott, Atkinson, Zhang, Macaulay, et al, 2021; Zhang et al, 2022) and many of them included international collaborations. Unsurprisingly, “multiple stressors” was the most frequently occurring keyword in our collection of articles (Figure 2d).…”
Section: Spatial and Temporal Distribution Of Identified Studiesmentioning
confidence: 99%